Validitas Lembar Kerja Siswa (LKS) Biologi Berbasis Pembelajaran Guided Inquiry - Nofayukisari Nofayukisari; Baiq Muli Harisanti; Ida Royani (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The existing worksheets (LKS) are generally less attractive, the images in the worksheets are less clear and colorless, no source of images are listed, the worksheets have not used a complete LKS format, such as instructions for using good worksheets for teachers as well as the students and the student worksheets used were not arranged neatly and systematically. The use of learning methods that are not quite right. Therefore it is necessary to have teaching materials related to the 2013 curriculum, one of which is teaching materials that have the guided inquiry learning method. It was drafted a student worksheet based on guided inquiry learning. This study validates the guided inquiry learning based biology student worksheet on the material of life organization systems. This study aims to determine the validity of biology student worksheets based on guided inquiry learning. The method used in this research is development (Research and Development). The design of development research is carried out through several stages that have been modified according to the needs of the researcher, namely: the definition stage (Define), the design stage (Design), and the development stage (Develop). At the defining stage, conducting a needs analysis, the design stage carried out the preparation of worksheets, and the development stage carried out expert validation. The instrument used in this study was a validation sheet. The data collection technique in this research is validation. The data analysis technique in this research is descriptive qualitative. The results showed that the validity of biology student worksheets based on guided inquiry learning was valid. The resulting worksheets are feasible for use with a validity level of 2.96. Thus, It can be concluded that the student worksheet is valid and suitable for use as teaching material.